M-Learning Aplikasi MIT App Inventor pada Materi Sistem Persamaan Linier Dua Variabel (SPLDV) Kelas VIII SMP Negeri 2 Pontianak Terhadap Keterampilan Berpikir Kritis - Saputra, Oky; Muchtadi, Muchtadi; Sandie, Sandie (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to develop M-Learning-based learning media using the MIT APP Inventor Application to improve students' critical thinking skills on the topic of two-variable linear equation system (SPLDV) in grade VIII of SMPN 2 Pontianak. The method used is research and development by involving 3 experts for material validation and 3 experts for media validation. The research subjects consisted of 29 grade VIII students of SMPN 2 Pontianak. The data collected includes validation sheets, student response questionnaires, teacher response questionnaires, and student critical thinking skills tests. The results of the study show that the MIT APP Inventor application-based learning media achieves a validity level of 81.61% (very valid), a practicality level of 86.76% (very practical), and an effectiveness level of 17% (quite effective). Thus, the MIT APP Inventor application is suitable to be used as a learning medium for grade VIII students of SMPN 2 Pontianak in facing SPLDV materials